Egy „jogfosztás” margójára - Fázsi, László; Fedor, Anett (Debreceni Jogi Műhely, 2012)
Under the topic of long-term criminal processes the study focuses on the role of the defenders, regarding the delays, in connection with Section 275 and 281 of the Criminal Process Code (Act XIX of 1998), amended by the Act CLXXXIII of 2010. Due to the authors, the misuse of the principle „right of defense”, is one of the significant reasons of the delays in criminal processes. Therefore they agree with the modifications, came into force as of March 1, 2011, which made more difficult to misuse the above mentioned principle. According to the modifications, now it is prohibited to postpone the hearing at the court because, no matter why, the defender could not take part at it. However, beside the positive evaluation of these modifications, the authors draw the attention of the legislator to the problems arising in the practice when the new rules will be applied. They highlight that the Subsection 3, Section 282 of the Criminal Process Code should have been modified, as well, and further amendments would also be necessary. It is said that the modifications, either already in force or still to be drafted, are of a high importance, beacause on one hand they warrant that the right of defense would not be misused from this point of view any more, and on the other hand they also support to maintain and ensure the fair criminal process and the attorneys’ respect, further on.